Coexistence of Behçet’s Disease and Ankylosing Spondylitis: A Case Report - Filiz Eser; Hatice Bodur; Ümit Seçkin (Archives of Rheumatology, 2008)
Whether Behçet’s disease (BD) is of the seronegative spondiloartropathy (SSpA) group has been a subject of debate for many years. On the other hand, the number of reported cases of coexisting BD and a disease of SSpA group has increased. Here we presented a patient with ankylosing spondylitis (AS) and BD to discuss the coexistence of these two diseases. (Rheumatism 2008 23: 69-71)